2011
DOI: 10.1007/s00415-011-6125-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discrimination thresholds in adult-onset primary torsion dystonia: an analysis by task type and by dystonia phenotype

Abstract: Adult-onset primary torsion dystonia (AOPTD) is an autosomal dominant disorder with markedly reduced penetrance. Sensory abnormalities are present in AOPTD and also in unaffected relatives, possibly indicating nonmanifesting gene carriage (acting as an endophenotype). The temporal discrimination threshold (TDT) is the shortest time interval at which two stimuli are detected to be asynchronous. We aimed to compare the sensitivity and specificity of three different TDT tasks (visual, tactile and mixed/visual-tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 24 publications
5
82
1
3
Order By: Relevance
“…Moreover, we demonstrated that CFFt is sensitive to manipulation by TMS plasticity inducing protocols. This new information may be useful for future studies in patients with movement disorders including dystonia [80][83] in which altered multimodal sensory temporal processing has been demonstrated.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, we demonstrated that CFFt is sensitive to manipulation by TMS plasticity inducing protocols. This new information may be useful for future studies in patients with movement disorders including dystonia [80][83] in which altered multimodal sensory temporal processing has been demonstrated.…”
Section: Resultsmentioning
confidence: 94%
“…The pervasive sensory deficits described in different forms of adult-onset focal dystonia and the fact that tactile deficits are present even in the absence of motor symptoms led to the hypothesis of a sensory endophenotype in focal dystonia (Bradley et al, 2012;Fiorio et al, 2003;Hutchinson et al, 2013), that could be a useful biological marker of genetic status. This hypothesis is mainly supported by the observation that deficits in somatosensory SDT and TDT are present also in some patients' unaffected relatives, who could carry a mutated known (e.g.…”
Section: Sensory Processingmentioning
confidence: 98%
“…Even higher TDTs, sufficient to differentiate from Parkinson patients, were reported in multiple system atrophy (Rocchi et al, 2013). In dystonia, increased TDT (Conte et al, 2014b, Bradley et al, 2012, Scontrini et al, 2009, Fiorio et al, 2008a, Fiorio et al, 2003, Sanger, et al, 2001, Bara-Jimenez, et al, 2000, Tinazzi et al, 1999) is not only prevalent, but considered to be an endophenotype in autosomal dominant primary torsion dystonia, seen even in unaffected carriers (Kimmich et al, 2011, Bradley et al, 2009, Fiorio et al, 2007). That TDT is highly associated with particular gene mutations has led to interest in developing TDT as a useful tool in performing genetic studies.…”
Section: Introductionmentioning
confidence: 99%